Acanthurus nigros günther, a valid species of surgeonfish, distinct from the Hawaiian A. nigroris Valenciennes - Randall, J.; Di Battista, Joseph; Wilcox, C. (University of Hawaii Press, 2011)
The Blueline Surgeonfish, Acanthurus nigroris Valenciennes, formerly considered as wide-ranging in the central and western Pacific, is restricted to the Hawaiian Islands. Acanthurus nigros GÄnther, type locality Vanuatu, is available for the sister species from the Pitcairn Islands west to the Great Barrier Reef and Caroline Islands. Although these two species are very similar in color, there are fin-ray and gill-raker differences, and the genetic difference (i.e., 4.12 % mtDNA cytochrome b sequence divergence) alone warrants species recognition.